2011
DOI: 10.1371/journal.pone.0020476
|View full text |Cite
|
Sign up to set email alerts
|

Using and Reporting the Delphi Method for Selecting Healthcare Quality Indicators: A Systematic Review

Abstract: ObjectiveDelphi technique is a structured process commonly used to developed healthcare quality indicators, but there is a little recommendation for researchers who wish to use it. This study aimed 1) to describe reporting of the Delphi method to develop quality indicators, 2) to discuss specific methodological skills for quality indicators selection 3) to give guidance about this practice.Methodology and Main FindingThree electronic data bases were searched over a 30 years period (1978–2009). All articles tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
1,476
3
27

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,430 publications
(1,613 citation statements)
references
References 41 publications
(44 reference statements)
16
1,476
3
27
Order By: Relevance
“…We employed a modified Delphi approach [12], drawing on our own expertise as anaesthetists with an academic interest in human factors, to develop the new medical tool.…”
Section: Stage 1: Development Of the Prototype Cmatmentioning
confidence: 99%
“…We employed a modified Delphi approach [12], drawing on our own expertise as anaesthetists with an academic interest in human factors, to develop the new medical tool.…”
Section: Stage 1: Development Of the Prototype Cmatmentioning
confidence: 99%
“…The technique is designed as a group exercise that aims to achieve a convergence of opinion that may prove very useful. [8][9][10][11][15][16][17][18][19] The interactions of experts may lead to a reduction in individual bias. The Delphi method is a wellrecognized tool for solving problems in healthcare, and it is increasingly being used to reach consensus around many topics in medicine, including education, development of clinical guidelines, and prioritization of research topics.…”
Section: Discussionmentioning
confidence: 99%
“…The Delphi method is a wellrecognized tool for solving problems in healthcare, and it is increasingly being used to reach consensus around many topics in medicine, including education, development of clinical guidelines, and prioritization of research topics. 16,17 It has been argued that the forecasting accuracy of the Delphi technique is clearly reliable. For example, a Delphi study involving medical doctors evaluating the forecasting application of the method revealed that, in 75% of cases, the estimated values proved to be less than 10% different from the values observed.…”
Section: Discussionmentioning
confidence: 99%
“…While no consensus recommendations exist for the structure of a modified Delphi panel, we modeled the structure of our Delphi technique on the recommendations reported by Boulkedid et al 65 in their 2011 systematic review of the topic, including: 1) the use of a preset level of percent agreement and stop criteria, 2) use of a 1 to 9 Likert rating scale, 3) two to three rounds, 4) heterogeneous panel, 5) and mixed qualitative and quantitative feedback.…”
Section: Content Validation Phasementioning
confidence: 99%
“…98 The size of the expert panel was based on recommended Delphi methodology and is similar in size to other Delphi panels described in the literature. 65 However, while a smaller panel is more advantageous in terms of discussion and consensus, the results may be limited by skewed sampling of experts. 99 An attempt was made to diminish this effect by inviting a diverse group of expert panelists to participate, in terms of years in practice, education level, sex, practice type and setting, and geographic location.…”
Section: Limitationsmentioning
confidence: 99%